Development of Constructivism-Base Student Work Sheets of Aldehydes and Ketone Materials for Organic Chemistry II Students - Hasnah Hasnah; Susilawati Susilawati; Maria Erna; Rini Rini (Universitas Riau, 2019)
Teaching materials that were applied previously in the form of MFIs are not yet constructivism-based. During the time, the applied student worksheet (LKM) is monotonic so that students are less motivated in the learning process, as the solution, a constructivism-based LKM need to be developed. The research aims to develop constructivismbased Student Worksheets on aldehyde and ketone material. This type of research was Research and Development with a 4-D development model which includes Definition, Design, Development, and Disseminate. This research was only carried out until the development stage and was followed by limited trials. The research was conducted at the FKIP University of Riau. The object of the research was constructivism-based LKM. The data analysis technique used in the study was descriptive statistical analysis, which was calculating the percentage of validation values. The average score of the assessment of the five aspects of the LKM feasibility by the validator team, which was didactic, constructs of feasibility of presentation, construct of linguistic, technical feasibility, characteristics of constructivism successively have a score of 98%, 100%, 99%, 100% and 100%, respectively. The average score of overall validation of constructivism-based Aldehyde and Ketone LKM is 99.39% with a valid feasibility category, meaning that the developed LKM are feasible to use in the real teaching.